PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE ROLE PLAYING BERBASIS PENDIDIKAN KARAKTER TERHADAP KOMPETENSI PENGETAHUAN IPS SISWA KELAS V SD NEGERI GUGUS KAPTEN KOMPYANG SUJANA DENPASAR BARAT - Ni Luh Sri Yuliani (Universitas Pendidikan Ganesha, 2018)
This research aimed to determine the influence of cooperative learning model type role playing based on character education against the competency knowledge of social science students fifth graders in SD Negeri Gugus Kapten Kompyang Sujana Denpasar Barat in years 2017/2018. This research is an experimental research with the research design is quasi-exsperimental design (nonequivalent control group design). The population in this research is all fifth graders in SD Negeri Gugus Kapten Kompyang Sujana Denpasar Barat in years 2017/2018 as many as 637 students. Research sample is determined by random sampling technique. The sample in this research is grade VC SD Negeri 9 Padangsambian as experimental group and grade VB SD Negeri 1 Padangsambian as control group. Social science knowledge competence control data is collected with instruments in the form of multiple choice test. Then the data is analyzed by t-test. The result of the analysis shows that there is a significant difference of social science knowledge competence among group of students who are tought using cooperative learning model type role playing based on character education and conventional learning of fifth graders in SD Negeri Gugus Kapten Kompyang Sujana Denpasar Barat in years 2017/2018. This is evidenced by the Tcount of = 9,079 and Ttable = 2,000 at the significant level of 5% with dk = n1+n2-2 (43+43-2=84). Similarly the average score of knowledge competence of social science students experimental group = 82,00 > = 65,01 average of social science knowledge competence of control group students. Thus it can be concluded that the application of cooperative learning model type role playing based on character education influence the knowledge competence of social science fifth grade in SD Negeri Gugus Kapten Kompyang Sujana Denpasar Barat in years 2017/2018.